Application of diversified teaching mode in ultrasound-guided interventional procedures for treatment of pain - JIA Dong-lin, LI Shui-qing, JIANG Jie, JIANG Ling (Jichu yixue yu linchuang, 2022)
Objective To explore the application effect of diversified teaching mode in ultrasound-guided interventional procedures for treatment of pain. Methods Thirty learners who studied in the Department of Pain, Peking University Third Hospital from January 2018 to December 2020 were enrolled as participants, and were divided into control group and observation group. The control group adopted conventional teaching mode, while the observation group adopted diversified teaching mode. The clinical skill assessments, teaching quality and satisfaction scores of the two groups were compared. Results The excellent and good rate of clinical skill assessments in the observation group was 93.3%, which was higher than that in the control group, which was 73.3%(P＜0.05). Scores of mastering basic theoretical knowledge, improving clinical thinking ability, motivating learning interests and improving disease diagnosis and treatment ability in observation group were higher than those in control group (P＜0.01). Conclusions Diversified teaching mode improves ultrasound-guided interventional pain management skills, and supports the capacity building of clinical treatment.The method may function as a innovative clinical training pathway for other medical schools and healthcare institutions.